Surface treatment of bulk and porous materials based on superelastic titanium alloys for medical implants. (2017) - Korobkova, Anastasia; Kazakbiev, Alibek; Zhukova, Yulia; Sheremetyev, Vadim; Dubinskiy, Sergey; Filonov, Mikhail
Abstract: The present study addresses two approaches in surface modification targeted at the enhancement of titanium implants' biocompatibility. The first one comprises alkali heat treatment leading to formation of amorphous sodium titanate layer that encourages bone growth. Alkali heat treatment conducted on Ti Grade 2 and Ti-22Nb-6Zr (at.%) in 5M NaOH solution at 60 °C for 24 hours and different heat treatments at 600 °C. The obtained surface layer on Ti Grade 2 is without cracks, but sample without heat treatment does not contain oxygen that promotes formation of sodium titanate. Layer on Ti-22Nb-6Zr is cracked after all heat treatments, but after 600 °C, 0.5 h there is more modified layer in terms of area and more sodium on the surface than after 600 °C for 1 h. The second approach comprises using porous metallic materials mimicking bone structure and properties. Due to the soft cellular structure of Ti foams, the surface porosity is often compromised by traditional machining methods which lead to surface smearing. The key idea to maintain the porous surface structure after the machining is to use an infiltrant material (wax) filling the foam before the machining and is chemically removed afterwards. The corresponding technological scheme has been developed and described.